ĐÁNH GIÁ HIỆN TRẠNG VÀ RỦI RO MÔI TRƯỜNG DO TÍCH TỤ HYDROCARBON THƠM ĐA VÒNG (PAH) TRONG TRẦM TÍCH LƯU VỰC HẠ LƯU SÔNG MÊ KÔNG - Nguyễn, Trọng Hiệp; Vũ, Thị Minh Châu; Lê, Đức Mạnh; Mai, Quang Tuyến; Nguyễn, Đức Thịnh; Trần, Thị Lệ Thu; Lê, Minh Tuấn; Nguyễn, Ngọc Phương; Nguyễn, Lê Kim Phụng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
MONITORING AND RISK ASSESSMENT OF POLYCYCLIC AROMATIC HYDROCARBON IN LOWER MEKONG BASIN SEDIMENTS A total of 61 sediment samples were collected from 22 locations along the Mekong River basin in Tien Giang, Ben Tre, Dong Thap and An Giang provinces. The correlation coefficient (R2) for each polycyclic aromatic hydrocarbon (PAH) was exceeded 0.995 with repeatability ranging from 5.7% to 12.5%, reproducibility from 9.4% to 12.8%, and process recovery rates between 82.8% and 114.6%. In addition, the detection limits of individual PAH ranged from 3.05 μg/kg to 37.8 μg/kg. The total content of 18 PAHs in sediment samples ranged from 27.6 µg/kg to 2,018 µg/kg, of which the majority were non-carcinogenic PAH (NCPAH) with concentrations of less than 622 µg/kg, while carcinogenic PAH (CPAH) accounted for a smaller proportion with concentrations under 572 μg/kg. The PAH4 group consisting of Benzo(a)pyrene, Benzo(a)anthracene, Benzo(b)fluoranthene, and Chrysene was deteted at low concentrations ranging from non-detectable levels to 560 μg/kg. Furthermore, the analysis at PAH composition in the sediment samples revealed that 2- to 3-ring aromatic PAHs were the most prevalent, constituting 46.22% of the total, followed by 4-ring aromatic PAHs at 31.4%. The environmental risk factor associated with PAH accumulation in the sediments was calculated to be below 0.75, indicating that the levels remain within the environmentally safe threshold.